To assess the knowledge, awareness, and perception of non-dentists offering orthodontic treatment among the Malaysian young adult population - Al Imran Shahrul; Ezzatul Raihan Pauzzi; Nor Diyanah Athirah Abas; Nurul Asyikin Yahya; Khairil Aznan Mohamed Khan; Murshida Marizan Nor (BMC, 2024)
Abstract Background The increasing number of young adults seeking cheaper and easily accessible orthodontic treatment from unlicensed practitioners in Malaysia poses significant risks to patients. Therefore, it is essential to evaluate their motivations and awareness regarding such practices. The objective of our study was to assess the knowledge, awareness, and perceptions of non-dentists offering orthodontic treatment among the Malaysian young adult population. Methods This was a cross-sectional study. An online self-administered questionnaire was distributed to Malaysian citizens aged 18-37 years. The questionnaire consisted of 11 questions that investigated their awareness of non-dentists offering orthodontic treatment, the harmful effects of braces fitted by non-dentists, and potential strategies to mitigate this phenomenon. Results The study was completed by 426 participants, predominantly Malay, with a mean age of 22.9 years. A total of 76.1% reported awareness of braces fixed by non-dentists, primarily through social media platforms such as Instagram and Facebook. Lower cost emerged as the predominant motive (83.6%) for opting for non-dentist orthodontic treatment, followed by no waiting list (48.8%). Notably, the majority of participants acknowledged the illegality (70%) and potential harm (77%) associated with non-dentists providing orthodontic treatment. Legal enforcement (53.1%) was identified as the preferred method for mitigating this practice. Occupation significantly influenced knowledge of illegal orthodontic treatment (p < 0.05), however no significant association was found for gender and level of education (p > 0.05). Conclusion The survey revealed that young adults are aware of and informed about non-dentists offering orthodontic treatment. While they identified cost as the primary reason for seeking such services, they also recognized legislation and public awareness through campaigns and social media as effective strategies to address this issue. Additionally, significant differences in legal awareness were observed among different occupational levels.